Web-Based Simulation on Physics Learning to Enhance Digital Literacy Skill of High School Students - Riki Perdana; Riwayani Riwayani; Jumadi Jumadi; Dadan Rosana (JIPF (Jurnal Ilmu Pendidikan Fisika), 2019)
The study aimed to investigate the effectiveness of Web-Based Simulation (WBS) on Physics learning to enhance digital literacy skills of Grade XI students in high school. The level of digital literacy skills of the students in the experiment and control group before and after they study using WBS learning and none was determined respectively. The comparison of their levels before and after the study was done to determine the effectiveness of the WBS learning. The participants of this study were 49 students of science class, with 14-16 age. The research design in this study were descriptive-comparison and pretest-posttest experimental design. Data analysis using Anova mixed design with significant 5%. The result of this study are level of students' digital literacy skill before learning process is generally very low; but after the treatment these skill was comparatively increased. In addition, there was a significant difference in the level of digital literacy skill of the classes where the WBS learning is the more effective than direct learning to enhance students’ digital literacy skill.